First Autologous Cell Therapy of Cerebral Palsy Caused by Hypoxic-Ischemic Brain Damage in a Child after Cardiac Arrest—Individual Treatment with Cord Blood - A. Jensen; E. Hamelmann (Case Reports in Transplantation)
Each year, thousands of children incur brain damage that results in lifelong sequelae. Therefore, based on experimental evidence, we explored the therapeutic potential of human cord blood, known to contain stem cells, to examine the functional neuroregeneration in a child with cerebral palsy after cardiac arrest. The boy, whose cord blood was stored at birth, was 2.5 years old and normally developed when global ischemic brain damage occurred resulting in a persistent vegetative state. Nine weeks later, he received autologous cord blood (91.7 mL, cryopreserved, 5.75×10e8 mononuclear cells) intravenously. Active rehabilitation (physio- and ergotherapy) was provided daily, follow-up at 2, 5, 12, 24, 30, and 40 months. At 2-months follow-up the boy’s motor control improved, spastic paresis was largely reduced, and eyesight was recovered, as did the electroencephalogram. He smiled when played with, was able to sit and to speak simple words. At 40 months, independent eating, walking in gait trainer, crawling, and moving from prone position to free sitting were possible, and there was significantly improved receptive and expressive speech competence (four-word sentences, 200 words). This remarkable functional neuroregeneration is difficult to explain by intense active rehabilitation alone and suggests that autologous cord blood transplantation may be an additional and causative treatment of pediatric cerebral palsy after brain damage.